Characteristics of Malignant Eyelid Basal Cell Carcinoma in Cicendo Eye Hospital Bandung from 2013 to 2015 - Yee She Hui; Raden Angga Kartiwa; Resti Gradia Dwiwina (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Basal cell carcinoma (BCC) has been proved to have the highest incidence among eyelid malignancies. Basal cell carcinoma is the most common invasive cancer in humans. It is capable of causing extensive tissue destruction. The aim of the study was to identify the characteristics of adult patients with malignant eyelid BCC in Cicendo Eye Hospital Bandung.Methods: A descriptive retrospective study was conducted to determine the characteristics of adult patients with malignant eyelid BCC in Cicendo Eye Hospital Bandung from March 2013 to October 2015. Age and sex distribution of the lesions, location and histopathological results of the tumors were stratified as variables. The inclusion criteria were patients over age of 20, histopathologically diagnosed with periocular BCC. Results: A total of 37 cases histopathologically diagnosed with periocular BCC were evaluated. Females had a slight predominance. The mean age was 61.7 years. The most common site was on the lower lid. The tumors occurred more on the left side. The most common histological subtype was represented by solid growth pattern.Conclusions: The majority of periocular BCC cases occur in females and elderly. Most tumors develop on the lower lid with a left-side preference and have a solid growth pattern histologically. [AMJ.2017;4(1):148–51] DOI: 10.15850/amj.v4n1.1037